2005
DOI: 10.1196/annals.1356.005
|View full text |Cite
|
Sign up to set email alerts
|

Immunoregulation of Cellular Life Span

Abstract: Our current studies focus on the molecular changes induced by aging. During aging, changes in proteins occur that alter their function and render them immunogenic. These "neoantigens" are recognized by physiologic autoantibodies. Physiologic autoantibodies and their corresponding antigens offer therapeutic strategies for disease intervention through the innate immune response. Early studies done in the 1970s showed humans and animals to have physiologic antibodies that bind to a neoantigen called senescent cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
64
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(74 citation statements)
references
References 93 publications
(253 reference statements)
10
64
0
Order By: Relevance
“…Vesicle formation appears to be accompanied by the breakdown of band 3 protein. It has been postulated that removal of senescent erythrocytes by macrophages is mediated by senescent cell-specific autoantigens originated on band 3, the anion exchanger and the major membrane protein of the erythrocyte (Kay, 2005). In accordance, Willekens et al (2008) confirmed that vesiculation is not only associated with the removal of membranebound hemoglobin, but is associated with generation of senescent cell antigen, a neoantigen that originates from band 3 after its breakdown in senescent red blood cells.…”
Section: Erythrocyte Morphologysupporting
confidence: 62%
“…Vesicle formation appears to be accompanied by the breakdown of band 3 protein. It has been postulated that removal of senescent erythrocytes by macrophages is mediated by senescent cell-specific autoantigens originated on band 3, the anion exchanger and the major membrane protein of the erythrocyte (Kay, 2005). In accordance, Willekens et al (2008) confirmed that vesiculation is not only associated with the removal of membranebound hemoglobin, but is associated with generation of senescent cell antigen, a neoantigen that originates from band 3 after its breakdown in senescent red blood cells.…”
Section: Erythrocyte Morphologysupporting
confidence: 62%
“…These neoantigens constitute targets for auto-Abs that, in association with enhanced complement components, culminate in phagocytosis (147)(148)(149)(150). According to several studies, anti-band 3 antibodies mediate this senescent RBC removal (149,150).…”
Section: Returning To Old Concepts To Propose New Immune Mechanisms Amentioning
confidence: 99%
“…Immunoblot analysis with antibodies against band 3 peptides indicated the existence of an altered band 3 in vesicles (Fig 4). A strong immunoreactivity was revealed by two antibodies to two closely related epitopes (aa 562-565 and aa 565-569) in the N-terminal part of the membrane domain (Table II), that participate in senescent cell antigen activity (Kay, 2005). These particular antibodies were mainly reactive with a protein of approximately 70 kDa in size.…”
Section: Vesiclesmentioning
confidence: 99%
“…The relationship between the data from the semiquantitative analysis of the immunoreaction and the specificity of the various antibodies for specific domains, suggested that some areas within the membrane are preferentially affected during erythrocyte ageing (Table II, Fig 4). Particularly, antibodies directed against epitopes in the N-terminal part of the membrane domain (aa 540-565) and, to a lesser extent, an antibody directed against the C-terminal part of the membrane domain (aa 840-911), that together constitute the senescent cell antigen (Kay, 2005), showed an age-related increase in reactivity (Table II). Interestingly, these very antibodies also showed a positive reaction with vesicle proteins (Table II).…”
Section: F L a Willekens Et Al ª 2008 The Authorsmentioning
confidence: 99%